ANALISIS FAKTOR-FAKTOR KESULITAN BELAJAR SISWA DALAM PEMBELAJARAN DARING (DALAM JARINGAN) PADA MATA PELAJARAN EKONOMI KELAS XII DI SMA NEGERI 1 KOTA JAMBI TAHUN AJARAN 2020/2021 - Rafiuni, Suci; Afrila, Diliza (SJEE (Scientific Journals of Economic Education), 2021)
Abstract This study aims to determine the factors of student learning difficulties in online learning in Economics class XII at SMA Negeri 1 Jambi City. This type of research is a descriptive study and a quantitative approach. The population in this study was 174 people. The sampling technique in this study was random sampling, so that 121 students were selected as the research sample. The data collection technique in this study was to distribute questionnaires to research respondents. The data analysis technique in this study is factor analysis with the SPSS For Windows Version 16 program. The results of this study indicate that (1) the learning difficulty variable is in the sufficient category with an average of 3.40 and the Respondents' Achievement Level (TCR) of 67.92. and (2) there are 11 (eleven) dominant factors that influence student learning difficulties, namely (a) factor 1 which is given the identity of the Learning Environment, (b) factor 2 which is given the identity of Learning Interests, (c) factor 3 which is given the identity of Talent, (d) factor 4 which is given the identity of Learning Motivation, (e) factor 5 which is given the identity of Learning Habits, (f) factor 6 which is given the identity of Intelligence, (g) factor 7 which is given the identity of Student Characteristics, (h) factor 8 which is given School climate identity, (i) factor 9 which is given the identity of the Learning Method, (j) factor 10 which is given the identity of Learning Tools, and (k) factor 11 which is given the identity of Family Roles. Keywords: Learning Difficulties.